2012
DOI: 10.1142/s0217751x12500972
|View full text |Cite
|
Sign up to set email alerts
|

Non-Abelian Vortex-String Dynamics From Nonlinear Realization

Abstract: Abstract. The dynamics of the non-Abelian vortex-string, which describes its low energy oscillations into the target D = 3 + 1 spacetime as well as its orientations in the internal space, is derived by the approach of nonlinear realization. The resulting action correlating these two sectors is found to have an invariant synthesis form of the Nambu-Goto-CP N −1 model actions. Higher order corrections to the vortex actions are presented up to the order of quartic derivatives. General p-brane dynamics in terms of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…The investigation of SUSY extensions of genuinely nonstandard kinetic terms has been resumed only recently [55]- [63] (see also [64]- [67] for related discussions), where this rising interest is partly owed to the fact that field theories with non-standard kinetic terms may be instrumental in the resolution of some enigmas of cosmology [68]- [80]. Concretely, in [56] we demonstrated that the baby Skyrme model in the O(3) formulation does have a N = 1 SUSY extension for arbitrary non-negative potential.…”
Section: Jhep05(2013)108mentioning
confidence: 99%
“…The investigation of SUSY extensions of genuinely nonstandard kinetic terms has been resumed only recently [55]- [63] (see also [64]- [67] for related discussions), where this rising interest is partly owed to the fact that field theories with non-standard kinetic terms may be instrumental in the resolution of some enigmas of cosmology [68]- [80]. Concretely, in [56] we demonstrated that the baby Skyrme model in the O(3) formulation does have a N = 1 SUSY extension for arbitrary non-negative potential.…”
Section: Jhep05(2013)108mentioning
confidence: 99%
“…Higher derivative corrections to the vortex effective theory was studied in Refs. [41,42]. If we calculate the next-to-leading order to the moduli approximation, we obtain four derivative terms in the CP N −1 Lagrangian [41].…”
Section: A Theory 3: Instantons As Twisted Closed Monopole Stringsmentioning
confidence: 99%
“…(28) in the original Lagrangian from the beginning. These terms would induce more general four derivative terms in the vortex effective theory [42]. Then, lumps become baby Skyrmions in CP 1 model with four derivative term [22,23].…”
Section: A Theory 3: Instantons As Twisted Closed Monopole Stringsmentioning
confidence: 99%
“…While a CP N −1 generalization of the anti-ferromagnetic type potential was considered before [42] and was found to admit parallel multiple domain walls [43] or domain wall junctions or networks [44,45], depending on parameters in the potential, a CP N −1 generalization of the ferromagnetic (XY-type) of the potential has not been studied thus far in the CP N −1 model. Skyrme-like terms in the CP N −1 model were studied before without [46,47] and with [48][49][50] supersymmetry. A CP 2 or CP N −1 generalization of the baby Skyrme model with an anti-ferromagnetic potential will admit vortex trimers or Nomers, respectively.…”
Section: Summary and Discussionmentioning
confidence: 99%